Climate-optimized flight planning can effectively reduce the environmental footprint of aviation in Europe at low operational costs - Abolfazl Simorgh; Manuel Soler (Communications Earth & Environment)
Abstract The non-CO2 climate impacts of aviation, such as ozone formation and contrail-cirrus, are highly sensitive to the location and time of emissions, underscoring the role of aircraft trajectories in mitigating their corresponding effects. We present a comprehensive analysis exploring the potential of climate-optimized flight planning to mitigate the aviation sector’s climate impact. We demonstrate that the effectiveness of flight planning in mitigating climate effects is closely tied to daily meteorological conditions. Therefore, smart adoption of climate-optimal trajectories, i.e., rerouting only under conditions where large climate benefits are achievable, effectively mitigates climate impact while maintaining operational feasibility through minimal changes to standard operations. Overall, for a subset of European flights, a reduction in climate impacts of 12.5% and 21.3% is achievable with an increase in operational costs of 0.2% and 2.0%, respectively. Seasonal variation is considerable, with summer showing the lowest climate mitigation potential and autumn the highest, linked to the likelihood of contrail formation. The findings suggest that flight planning is most effective at mitigating the climate impact of contrails, accounting for over 80% of the net mitigation potential. Our work offers aviation policymakers a clearer understanding of the potential climate benefits achievable through flight planning.